Clinical and histological characteristics of Hodgkin's lymphoma in the Syrian coastal region - عاقل, سامر (Latakia University Journal -Medical Sciences Series, 2021)
Most data about cancer in Syria are estimated. This retrospective study aimed to analyze the clinical and pathologic characteristics of Hodgkin lymphoma (HL) and their impact on the survival in the Syrian Coastal Zone. All new Hodgkin lymphoma patients with completed data who lived in SCZ and registered in the period 2010-2014 with the log book of the Unit for Radio- and Chemotherapy of Tishreen University Hospital (URCTUH) in Latakia, which was the only cancer unit in the SCZ between 2006-2016. The age, sex, histological subtypes, treatment group, recurrence and death when happened for each case were documented. 187 new cases of the SCZ-citizens were diagnosed with Hodgkin lymphoma (HL) and referred to the URCTUH in the period 2010-2014. Just 169 cases were enrolled because of uncertain or incomplete data in 18 files. 89 (52.7%), 80 (47.3%) were males and females respectively. Male: female ratio was 1.01. The histological subtypes were as the following: 91(53.8%), 52(30.8), 9(5.3%), 8(4.7%) and 9(5.3%) for nodular sclerosing (NSHL), mixed cellularity (MCHL), lymphocyte rich(LRHL), lymphocyte depleted (LDHL) and nodular lymphocyte predominant (NLPHL) respectively. Treatment groups based on European Organization for Research and Treatment of Cancer (EORTC) classification: 31(18.3%), 68 (40.2%) and 70 (41.4%) for limited stage (L), intermediate stage (I) and advanced stage (A). The follow-up was ended on 15 Dec 2020 and 40 deaths were reported. 26 (29.2%) and 14 (17.5%) were males and females respectively. 5 years OS was 74.4% in males, 8.74% in females, and 81.1% in both sexes. It was also significantly higher in younger patients, non-advanced stages and non-relapsed cases. Systematic monitoring and analysis of Hodgkin lymphoma data would provide clinical, pathological and prognostic information which could improve the health care of these patients and the outcomes for this malignancy in Syria.